Analysis of Challenges and Opportunities for Improving the Health System in Afghanistan: Innovative Approaches and Sustainable Solutions - Mazloum Yar, Fayaz Gul (Jurnal Sosial Teknologi, 2024)
This research explores the challenges and opportunities for improving the health system in Afghanistan. The main objective is to identify the major issues within the healthcare system and propose sustainable solutions to enhance the quality of health services. Using a mixed-method approach (qualitative and quantitative), data were collected through semi-structured interviews with experts and a review of credible scientific sources. The findings indicate that a lack of healthcare infrastructure, a shortage of specialized human resources, and management issues are among the primary challenges facing Afghanistan's healthcare system. Additionally, opportunities such as international support and utilizing modern technologies in healthcare have been identified. The study concludes that investment in infrastructure, human resource training, and strengthening international collaborations are essential to improve the healthcare situation in Afghanistan. The study's recommendations emphasize the importance of investments in infrastructure, comprehensive training for health workers, and international partnerships to strengthen service delivery. This analysis provides practical insights for policymakers and international organizations, which could ultimately help build a more resilient health framework in Afghanistan.